Proceedings of SPE International Symposium on Oilfield Chemistry 2005
DOI: 10.2523/93273-ms
|View full text |Cite
|
Sign up to set email alerts
|

Foams for Controlling Water Production

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThere is a great interest in the oil production industry in relative permeability modifiers (RPM) that can preferentially reduce water production without significantly affecting oil production. Various hydrophilic polymers have been studied for their RPM properties. This paper shows the potential of foam as RPM. Foams stable for a long time in presence of flowing water were developed using polymeric surfactants. Scale-up calculations show foam lifetimes long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 15 publications
(21 reference statements)
2
13
0
Order By: Relevance
“…It should be noted that the theories introduced thus far (i.e., E, S, and B coefficients) have primarily been developed through observations of foam films and oil under very controlled circumstances and therefore may not correlate equally well to all foam tests applied with oil present. Experimental studies indicate varying degree of correlation between foam properties in bulk and porous media in the presence of oil and the calculated coefficients (Andrianov et al, 2011;Arnaudov et al, 2001;Basheva et al, 2000;Bergeron, 1993;Bhide et al, 2005;Dalland et al, 1992;Mannhardt et al, 2000;Raterman, 1989;Rohani et al, 2014;Vikingstad et al, 2006). Several of the abovementioned laboratory studies have also demonstrated that foam performance in the presence of oil can be strongly influenced by the particular test method, procedures and conditions applied.…”
Section: Bridging Coefficientmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that the theories introduced thus far (i.e., E, S, and B coefficients) have primarily been developed through observations of foam films and oil under very controlled circumstances and therefore may not correlate equally well to all foam tests applied with oil present. Experimental studies indicate varying degree of correlation between foam properties in bulk and porous media in the presence of oil and the calculated coefficients (Andrianov et al, 2011;Arnaudov et al, 2001;Basheva et al, 2000;Bergeron, 1993;Bhide et al, 2005;Dalland et al, 1992;Mannhardt et al, 2000;Raterman, 1989;Rohani et al, 2014;Vikingstad et al, 2006). Several of the abovementioned laboratory studies have also demonstrated that foam performance in the presence of oil can be strongly influenced by the particular test method, procedures and conditions applied.…”
Section: Bridging Coefficientmentioning
confidence: 99%
“…Foams can also reduce water flow. Several authors indicate that foams can survive in laboratory corefloods, at least in a weakened form, against several pore volumes of liquid injected (Aarra et al, 2011;Bernard et al, 1965Bernard et al, , 1980Bhide et al, 2005;Du et al, 2007;Nguyen et al 2009;Parlar et al, 1995;Seright, 1996;Zeilinger et al, 1995). Reduced foam stability to subsequent liquid injections has been discussed in terms of surfactant dilution, gas expansion and gas dissolution into the injected liquid phase.…”
Section: Water Blocking Abilitiesmentioning
confidence: 99%
See 3 more Smart Citations